One Health integrated strategies for sustainable control of Opisthorchis viverrini infections in rural endemic areas of Thailand - Suksanti Prakobwong; Lakhanawan Charoensuk; Suwit Chaipibool; Kacha Chedtabud; Umawadee Laothong; Apiporn T. Suwannatrai; David Blair; Somchai Pinlaor (Infectious Diseases of Poverty)
Abstract Background Opisthorchiasis, caused by Opisthorchis viverrini, poses a significant health risk in northeastern Thailand, increasing the prevalence of cholangiocarcinoma. This study implemented a One Health integrated strategy, targeting human, animal, and environmental factors to reduce O. viverrini prevalence and transmission in an endemic region. Methods The study was conducted from 2016 to 2022 in the Huay Luang Reservoir area, Udon Thani Province, Thailand and enrolled 5412 participants. Annual stool examinations were conducted and participants found to be infected with O. viverrini received anthelmintic treatments. Other intervention methods included health education, snail control, veterinary care, sanitation improvements, training of health volunteers, creating a learning center and liver fluke-free fish production. Annual data on prevalence, infection intensity, and reinfection rates were collected. Student’s t-test, one-way ANOVA, Chi-square test, or Fisher’s exact test were used to compare data across the study years, with statistical significance set at P < 0.05. Results The One Health strategy significantly reduced O. viverrini prevalence in humans from 14.1% in 2016 to 0.9% in 2022, with O. viverrini-egg intensity decreasing from 76.9 to 25.5 eggs per gram (EPG) (P < 0.001). Reinfection rates decreased significantly from 17.4% in 2016 to 9.7% in 2022 following the implementation of the program (P = 0.003). Among reservoir hosts, infections in dogs and cats significantly decreased from 21.3% to 3.8% (P < 0.001). In cyprinoid fish, metacercarial prevalence significantly decreased from 21.9% to 2.2% (P < 0.001). Awareness of transmission routes rose from 45.1% to 82.6%, and raw fish consumption decreased from 52.4% to 12.3%. Biological control reduced Bithynia snail densities from 30 to under 5 snails/m2, while sanitation interventions increased toilet use from 31.7% to 87.1%. A local fish-processing enterprise enhanced food safety and income. Health volunteers engaged 94% of households, and a learning center trained 250 individuals and hosted site visits. Conclusions The One Health strategy effectively and sustainably limited O. viverrini infections and reinfections, demonstrating the potential of One Health as a model for zoonotic parasite control in other endemic areas.